2016
DOI: 10.1615/critrevimmunol.2016018175
|View full text |Cite
|
Sign up to set email alerts
|

Natural IgM and the Development of B Cell-Mediated Autoimmune Diseases

Abstract: Most serum immunoglobulin M (IgM) is “natural IgM,” which is produced apparently spontaneously by a distinct subset of B cells requiring no exogenous antigenic or microbial stimuli. Natural IgM is an evolutionarily conserved molecule and reacts with a variety of epitopes expressed on both self- and non-self antigens. It has long been understood that secreted (s) IgM contributes to the removal of altered self-antigens, such as apoptotic and dying cells. As we outline in this review, it is thought that this sIgM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 122 publications
0
49
0
Order By: Relevance
“…Using Ig‐allotype‐disparate B cells, we were able to differentiate sIgM binding from IgM–BCR surface expression and showed constitutive binding of sIgM onto the cell surface of B cells in vivo, which was reduced in the absence of the FcµR . Studies in transfected HeLa cells, as well as primary mouse B cells, showed that sIgM binding to surface‐expressed FcµR caused the rapid internalization and degradation of the complex through the endocytic pathway, a process that in CLL was shown to depend on the state of FcµR glycosylation . Interestingly, some sIgM uptake was shown to occur also in the absence of the FcµR, suggesting that not all sIgM internalization is mediated by the FcµR .…”
Section: Receptors That Bind Igmmentioning
confidence: 98%
See 3 more Smart Citations
“…Using Ig‐allotype‐disparate B cells, we were able to differentiate sIgM binding from IgM–BCR surface expression and showed constitutive binding of sIgM onto the cell surface of B cells in vivo, which was reduced in the absence of the FcµR . Studies in transfected HeLa cells, as well as primary mouse B cells, showed that sIgM binding to surface‐expressed FcµR caused the rapid internalization and degradation of the complex through the endocytic pathway, a process that in CLL was shown to depend on the state of FcµR glycosylation . Interestingly, some sIgM uptake was shown to occur also in the absence of the FcµR, suggesting that not all sIgM internalization is mediated by the FcµR .…”
Section: Receptors That Bind Igmmentioning
confidence: 98%
“…The polymeric immunoglobulin receptor (pIgR) is a highly conserved glycosylated receptor of about 81 kDa that is expressed principally by mucosal epithelial cells. The receptor binds both, dimeric IgA as well as pentameric sIgM via recognition of the J‐chain . The main function of the pIgR appears to be linked to the transepithelial transport of dimeric IgA, generated by plasma cells in the mucosal lamina propria, across the epithelial cell layer.…”
Section: Receptors That Bind Igmmentioning
confidence: 99%
See 2 more Smart Citations
“…Normal individuals produce F I G U R E 2 Tolerance by clonal deletion in ABO-incompatible transplantation. 39 43,44 IgM autoantibodies control complement activation, do not mediate cytolysis at 37°C and scavenge C3 and C4 complement components. The figure depicts an example.…”
Section: S Pace and Time: A Fourth D Imen S I On Of B Cell Toler An Cementioning
confidence: 99%